Distinguishing cell–cell complexes from dual lineage cells using single‐cell transcriptomics is not trivial. Issue 7 (20th May 2022) - Burel, Julie G.; Chawla, Ashu; Greenbaum, Jason A.; Peters, Bjoern
Abstract: In their recent correspondence, Jie et al. strongly defend that the DE cell population they discovered are always dual lineage co‐expressing cells and not complexes of B cells and T cells, which we have previously described as frequently present in single‐cell RNA sequencing data. Here, we respond to the specific arguments made in their correspondence. Specifically, we demonstrate that the presence of a gene signature in a given cell population is not enough to ascertain that it does not contain cell–cell complexes, or that it represents a biologically distinct cell type. We also show that the gene signature of DE cells contains several genes from the myeloid lineage, suggesting either that their DE cells are a triple‐lineage co‐expressing cell, or a three‐component cell aggregate. Finally, we identify multiple transcriptomic features of DE cells that correspond to B cell‐T cell complexes, namely the presence of lower average expression of B‐ and T‐cell specific genes, and a higher number of detected genes per cell. Taken together, our results demonstrate that solely based on their scRNAseq profile, it is not possible to ascertain that DE cells are dual expressing cells and not cell–cell complexes.